Micronutrient Supplementation and Socioeconomic Determinants among Pregnant Women in Tobruk, Libya: A Cross-Sectional Analysis - Lemamsha, Hamdi; Akrim, Taweda; El Hemiedy, Rehab; Mohamed, Mostafa; Randhawa, Gurca (Sharwes Scientific Journal, 2025)
Nutritional supplementation during pregnancy is essential in preventing maternal and neonatal complications such as anemia, low birth weight, and vitamin D deficiency. This cross-sectional study examined supplement adherence among 1,000 pregnant women attending antenatal care at four public health facilities in Tobruk, Libya. Data were collected using structured, interviewer-administered questionnaires incorporating validated scales on demographics, supplement use, pregnancy trimester, and trusted information sources. Analysis revealed high overall adherence, particularly in later pregnancy stages. Women with post-secondary education (OR = 1.74, p < 0.001) and higher household income (OR = 1.51, p = 0.002) were significantly more likely to use supplements. Supplement intake increased with trimester progression, with the third trimester showing the highest adherence (OR = 1.63, p = 0.001). Receiving guidance from healthcare professionals strongly influenced consistent use (OR = 1.82, p < 0.001), with participants expressing high trust in medical advice. However, some uncertainty was reported regarding supplement needs at different pregnancy stages. The findings indicate that educational level, financial stability, and professional guidance are key enablers of supplement adherence in this population. Improving antenatal strategies through accessible, trimester-specific education and equitable access to supplements could enhance maternal health outcomes in underserved regions like Tobruk.